Analysis of quinolinequinone analogs with promising cytotoxic activity against breast cancer - YILMAZ GÖLER, AYŞE MİNE (My University, 2023)
It is quite challenging to find out bioactive molecules in the vast chemical universe. Quinone moiety is a unique structure with a variety of biological properties, particularly in the treatment of cancer. In an effort to develop potent and secure antiproliferative lead compounds, five quinolinequinones (AQQ1-5) described previously have been selected and submitted to the National Cancer Institute (NCI) of Bethesda to envisage their antiproliferative profile based on the NCI Developmental Therapeutics Program. According to the preliminary in vitro single-dose anticancer screening, four of five quinolinequinones (AQQ2-5) were selected for five-dose screening and they displayed promising antiproliferative effects against several cancer types. All AQQs showed a excellent anticancer profile with low micromolar GI50 and TGI values against all leukemia cell lines, some non-small cell lung and ovarian cancer, most colon, melanoma, and renal cancer, and in addition to some breast cancer cell lines. AQQ2-5 reduced the proliferation of all leukemia cell lines at a single dose and five additional doses, as well as some non-small cell lung and ovarian cancer, the majority of colon cancer, melanoma and renal cancer, and some breast cancer cell lines. This motivated us to use in vitro, in silico, and in vivo technologies to further investigate their mode of action. We investigated the in vitro cytotoxic activities of the most promising compounds, AQQ2 and AQQ3, in HCT-116 colon cancer, MCF7 and T-47D breast cancer, and DU-145 prostate cancer cell lines, and HaCaT human keratinocytes. Concomitantly, IC50 values of AQQ2 and AAQ3 against MCF7 and T-47D cell lines of breast cancer, DU-145 cell lines of prostate cancer, HCT-116 cell lines of colon cancer, and HaCaT human keratinocytes were determined. AQQ2 exhibited anticancer activity through the induction of apoptosis and caused alterations in the cell cycle. In silico pharmacokinetic studies of all analogs have been carried out against ATR, CHK1, WEE1, CDK1, and CDK2. In addition to this, in vitro ADME and in vivo pharmacokinetic profiling for the most effective AAQ (AAQ2) have been studied.
Keywords: Biyomedikal Mühendisliği; Yaşam Bilimleri; Biyoteknoloji; Moleküler Biyoloji ve Genetik; Sitogenetik; Kimya; Temel Bilimler; Mühendislik ve Teknoloji; Biomedical Engineering; Life Sciences; Biotechnology; Molecular Biology and Genetics; Cytogenetic; Chemistry; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Mühendislik; Mikrobiyoloji; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; BİYOTEKNOLOJİ VE UYGULAMALI MİKROBİYOLOJİ; MÜHENDİSLİK, BİYOMEDİKAL; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); Life Sciences (LIFE); ENGINEERING; CHEMISTRY; MOLECULAR BIOLOGY & GENETICS; MICROBIOLOGY; BIOCHEMISTRY & MOLECULAR BIOLOGY; BIOTECHNOLOGY & APPLIED MICROBIOLOGY; ENGINEERING, BIOMEDICAL; Biyomühendislik; Fizik Bilimleri; Biyokimya; Genel Kimya; Moleküler Tıp; Moleküler Biyoloji; Bioengineering; Physical Sciences; Biochemistry; General Chemistry; Molecular Medicine; Molecular Biology; ADME; breast cancer; cytotoxicity; molecular docking